1454 The Challenges of Consent and COVID-19: Analysis of Documentation of Risk of Hospital Acquired COVID-19 Infection in a District General Hospital. (12th October 2021) - Davis, H; Mishra, S; Cooke, J
Abstract: Background: The COVID-19 pandemic has been a challenging time for society and raised further challenges for medical practice. It poses a new material risk to any hospital admission or procedure, and consenting practice must modify to accommodate this. Aim: To assess the documentation of the risk of COVID-19 infection and associated morbidity in consenting practice, using the existing consent form as benchmark, for patient's undergoing general surgical procedures under general anaesthesia. Method: Retrospective case-note analysis of 41 general surgical inpatient consent forms and operation notes during April 2020. Data were gathered on multiple points mentioned in Royal College of Surgeons (RCS) guidance. This includes documentation of risk of COVID-19 infection, the patient's diagnosis, other risk documentation, peri-operative lifestyle advice and likelihood of success. Results: Of 41 cases, 16 (39%) had risk of chest infection documented. Of these 16, 10 (63%) specified COVID-19 in the risk documentation. Further, morbidity related to COVID-19 was documented in 4 out of 41 (10%) cases identified. Conclusions: A material risk is classified as anything that poses substantial risk to a patient, and it is vital that they are made aware of this prior to undertaking any form of medical intervention. This study demonstrates deviation from RCS guidance, and the results have been discussed and distributed within the general surgical department. Advice has been communicated regarding improvements required in consenting practice from the clinical lead. We aim to re-audit practice in the coming months.